Coordonarea afacerilor europene la nivel naţional. Mecanisme de colaborare între Guvern şi Parlament în domeniul afacerilor europene. Studiu comparativ în statele membre UE - Iordan Gheorghe Bărbulescu; Oana Andreea Ion; Nicolae Toderaş (European Institute of Romania, 2013)
– In this study, we analyse the manner of developing a particular system of coordination of European affairs at national level, as well as its efficiency, the aim being to provide suggestions for improving it. The introductory section highlights the need for such a study, given the current political and institutional context of Romania, and it states the objectives of the study. Special attention is given to presenting the theoretical approach (expressing, on the one hand, the authors' vision that European affairs - distinctly from foreign affairs - are part of the complex governance process specific for the European Union (EU) and, on the other hand, operationalizing the idea of efficiency within a national system for coordinating European affairs, etc.) and the research methodology (reasons for choosing a comparative research design to support the presented arguments, as well as the qualitative research performed). In the first part, the paper also provides information on the legislative and institutional configuration of the EU, following the entry into force of the Lisbon Treaty, because the novelties and reforms brought by this regulatory framework (supperior to the one of the Nice Treaty, but inferior to the proposals stipulated within the Constitutional Treaty) have a direct impact on designing the structure for coordinating European affairs in the Member States. Given that in Romania the European affairs coordination system was initially inspired by the French model, while later suffering a series of institutional changes (some inspired by models from other EU states), an important part of the study addresses the need to know, from a comparative perspective, the best practices in European affairs coordination and cooperation mechanisms in other EU Member States. [...]
Keywords: 330; EU-Politik; Rumänien